Plasma Cell Neoplasms of Paranasal Sinuses: Two Case Reports - Mutlu, Merve; Arslan, Hande; Özdemir, Doğukan; Mehel, Dursun; Akgül, Gökhan (The turkish journal of ear nose and throat, 2024)
Sinonasal system malignancies are rare, constituting only 1% of all malignancies and less than 5% of head and neck malignancies. The common form of plasma cell dyscrasias is called multiple myeloma (MM), and the localized forms are called solitary bone plasmacytoma and extramedullary plasmacytoma (EMP). EMP constitutes 3-4% of malignant plasma cell dyscrasias and 1% of all head and neck tumors. 90% of EMP cases occur in the head and neck region, because the nasal and paranasal sinus regions are rich in plasma cells at around 75%. This study aims to present two different cases of plasma cell tumors presenting in the paranasal region. Based on the imaging studies, the first case is seen to have been diagnosed as MM due to bone marrow involvement and to have received systemic chemotherapy treatment, whereas the second case is seen to have undergone endoscopic total excision of the lesion due to the absence of systemic involvement. In the first case, MM was considered to have gone into remission in the sixth month after chemotherapy; however, the patient died one year after diagnosis. In the second case, no recurrence was detected during the fifth year postoperative follow-up. As a result, patients who show sinonasal symptoms should be examined in detail.